A single bout of downhill running attenuates subsequent level running-induced fatigue - de Oliveira Assumpção, Claudio [UNESP]; Barreto, Renan Vieira [UNESP]; de Lima, Leonardo Coelho Rabello [UNESP]; Cardozo, Adalgiso Coscrato [UNESP]; de Lima Montebelo, Maria Imaculada; Catarino, Helen Reinhart Camargo; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sergio [UNESP] (Springer Nature, 2020)
Fatigue can be defined as exercise-induced strength loss. During running, fatigue can be partially explained by repetitive low-intensity eccentric contractions-induced muscle damage (EIMD). Previous studies showed that a bout of downhill running (DR) attenuated subsequent EIMD. Thus, we tested if a 30-min DR bout would attenuate fatigue induced by subsequent 60-min level running (LR). Twenty-seven male college students were randomly allocated to an experimental (EXP) or a control (CON) group. All participants performed LR on a treadmill at 70% of the velocity (vVO2peak) corresponding to peak oxygen uptake (VO2peak). Only EXP performed a 30-min DR (− 15%) on a treadmill at 70% vVO2peak fourteen days before LR. Indirect EIMD markers and neuromuscular function were assessed before, immediately and 48 h after DR and LR. Knee extension isometric peak torque (IPT) decreased (− 36.3 ± 26%, p < 0.05) immediately following DR with full recovery reached 48 h post-DR. Muscle soreness developed (p < 0.05) immediately (37 ± 25 mm) and 48 h (45 ± 26 mm) post-DR. IPT and rate of torque development (RTD) at late phases (> 150 ms) from the onset of muscle contraction decreased significantly (− 10.7 ± 6.1% and from − 15.4 to − 18.7%, respectively) immediately after LR for the CON group and remained below baseline values (− 5.6 ± 8.5% and from − 13.8 to − 14.9%, respectively) 48 h post-LR. However, IPT and late RTD were not significantly affected by LR for the EXP group, showing a group x time interaction effect. We concluded that a single DR bout can be used to attenuate fatigue induced by a LR performed fourteen days after.